Research Note: Histopathology of Puccinia philippinensis Syd. & P. Syd, A Fungus that Causes Leaf Rust Disease to Cyperus rotundus L. - Donayre, Dindo King M.; Minguez, Lucille T. (Annals of Tropical Research, 2016)
Cyperus rotundus L., popularly known as purple nutsedge, mutha or barsanga, is a weed problem in most crop productions due to its prolific underground parts that permit rapid production of multiple young sprouts in the soil. Yield losses in many crops due to competition by C. rotundus range from 35 to 90%. Puccinia philippinensis, on the other hand, is a potential biological control against C. rotundus. Its anatomy of infection inside tissues of the weed, however, is still very much unexplored. This study was conducted to determine the histopathology of leaf rust disease caused by P. philippinensis inside leaf tissues of C. rotundus. Methods such as staining embedding, and mounting of leaves with structures of the rust fungus were conducted using the standard staining equipment, glasswares, and chemicals. Microscopic examination revealed that the histopathology of rust disease in leaves of C. rotundus started with swelling to the development of P. philippinensis’s uredinium in the lower epidermis. The event was followed by the development of numerous urediniospores that came from the uredinia. Lower epidermis of C. rotundus was ruptured due to pressing and pushing out of the urendiniodpores. Urendiniospores P. philippinensis were sub-globose to globose in shape measuring 13 x 16μ spores-1.